Macro-Financial Linkages in Shallow Markets : Experience from the African Department's Pilot Countries. (Departmental Papers; Departmental Paper ;, 2018)
This paper assesses and disseminates experiences and lessons from low-income countries (LICs) in Sub-Saharan Africa that were selected by the Africa Department in 2015-16 as pilots for enhanced analysis of macro-financial linkages in Article IV staff reports. The paper focuses on the common characteristics across the pilot countries and highlights the tools used in the analysis, the challenges encountered, and the solutions deployed in overcoming them.